Back to basics: can unstructured camping promote wellbeing?. Issue 1 (10th April 2017) - Morrow, Rosie; Rodriguez, Alison; King, Nigel
Abstract : Purpose: The purpose of this paper is to explore the perceived wellbeing benefits of the unstructured camping experience for young adults. Design/methodology/approach: This is a cross-sectional descriptive phenomenological study. Young adults between the ages of 21 and 30 years with recent experiences of camping were invited to participate in the study. A descriptive phenomenological approach was taken, involving photograph-guided semi-structured interviews and Colaizzi's seven-stage analysis framework. Ethical approval was granted by the university where the study was managed. Findings: Four female participants were interviewed; each interview lasted approximately 60 minutes in duration. Unstructured camping holidays were perceived to heighten general perceptions of health and wellbeing. Five themes emerged: "Getting away", "Appreciation of the Natural Environment", "Relationship Maintenance", "Tranquility and Relaxation" and "Freedom and Adventure/Exploration". The unstructured nature of the activity encouraged participant's freewill to appreciate the natural environment and to engage in physical activity. Escape from everyday stressors to a tranquil environment provided the space and time to think and talk, relax and be active. Originality/value: Green care initiatives could use the unstructured camping experience, or what the authors have framed as the "back to basics" model of camping, as a tool to promote general health and wellbeing in clinical and non-clinical young adult populations. Further research is needed to substantiate the evidence base, especially to probe further around the benefits of the spontaneity of the "back to basics" camping experience, in contrast to the structured group camp experiences the authors advocate in the UK and overseas for children's leisure or health purposes.